2015
DOI: 10.1016/j.freeradbiomed.2015.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Functional polymorphisms in Nrf2: implications for human disease

Abstract: Nuclear factor (erythroid derived)-2 like 2 (NFE2L2), also known as nuclear factor erythroid 2 (NF-E2)-related factor 2 (Nrf2), is a ubiquitous transcription factor essential for protecting cells and tissues from oxidative stress-induced injury. Positional cloning and studies with Nrf2 knockout mice have identified important roles for this transcription factor in disease phenotypes for many organ systems. Studies have also characterized the means through which human Nrf2 is regulated and the mechanisms of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 78 publications
(110 reference statements)
1
50
0
1
Order By: Relevance
“…Functional polymorphisms in NFE2L2 that diminish expression of Nrf2 have been linked with several diseases [reviewed in ref. (90)]. Nrf2 transactivation is subject to epigenetic regulation that can be suppressed, with a consequence of inhibiting Nrf2 target gene expression (1,9193).…”
Section: Resultsmentioning
confidence: 99%
“…Functional polymorphisms in NFE2L2 that diminish expression of Nrf2 have been linked with several diseases [reviewed in ref. (90)]. Nrf2 transactivation is subject to epigenetic regulation that can be suppressed, with a consequence of inhibiting Nrf2 target gene expression (1,9193).…”
Section: Resultsmentioning
confidence: 99%
“…7 E ). This study has significant clinical relevance because of the association of Nrf2 and MT gene polymorphisms for several diseases, including cardiovascular diseases (45,46). Once we refine the relationship of Nrf2 with MT in diabetes, we can explore strategies that upregulate MT and/or Nrf2 for patients with genetic polymorphisms, such as via SFN and/or zinc to induce cardiac protection.…”
Section: Discussionmentioning
confidence: 99%
“…An excellent review on this topic reported in 2015 up to 18 single-nucleotide polymorphisms (SNPs), most of them in the 59 regulatory region and in intron 1 (Cho et al, 2015). Several of these SNPs might constitute functional haplotypes that are associated with risk at onset or progression of chronic diseases.…”
Section: B Positioning Nuclear Factor (Erythroid-derived 2)-like 2 Amentioning
confidence: 99%